Zwischen Ost und West: Zur Druckgeschichte von Schimon Günzburgs jiddischer Brauchsammlung - Raspe, Lucia (Aschkenas, 2020)
Shimʻon Günzburg’s Yiddish collection of customs, first brought to press in Venice in 1589 and reprinted dozens of times over the following centuries, is often considered a mere translation of the Hebrew Minhagim put together by Ayzik Tyrnau in the 1420s. Another claim often made about the book is that, although it was first printed in Venice, it was intended less for the Italian book market than for export. This article sets out to test these assumptions by examining Günzburg’s compilation from the perspective of minhag, or prayer rite. Drawing on Yiddish manuscripts preserved from sixteenth-century Italy, as well as early printed editions overlooked by scholars, it argues that Günzburg’s Minhogim are, in fact, more Italian than has been recognized. It also points up their potential for a comparative history of Ashkenazic book culture across the political and linguistic borders of Europe.